PENGARUH MEDIA SOSIAL TERHADAP INTERAKSI SOSIAL SISWA DI SMP NEGERI 1 DASUK - Putri Damayanti; Anis Tri Yuliana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the effect of social media on students' social interaction at SMP Negeri 1 Dasuk. The study applied a quantitative associative design using questionnaire data from 28 respondents. The independent variable was social media use, while the dependent variable was students' social interaction. Each variable was measured using 25 Likert-scale items. Data analysis followed SPSS-style statistical procedures, including validity testing, reliability testing, descriptive statistics, normality testing, simple linear regression, t-test, F-test, and coefficient of determination. The instrument test showed that all items were valid because the item-total correlation values exceeded the r table value of 0.374. The reliability coefficients were very high, with Cronbach's Alpha of 0.969 for social media and 0.977 for social interaction. The residual normality test was fulfilled with Shapiro-Wilk Sig. = 0.510. The regression results showed R = 0.723, R Square = 0.523, F = 28.520, t = 5.340, and Sig. = 0.000. These results indicate that social media has a positive and significant effect on students' social interaction in this sample. Thus, social media use explains 52.3% of the variance in students' social interaction, while 47.7% is influenced by other factors outside the model.